The Relationship Between Psychosocial Factors and Quality of Working Life Among Information Systems Personnel - Rethinam, Guna Seelan (2004)
Increasing demand against the limited supply has forced the IS personnel to be responsible for multitasking with a higher workload. This trend appears to exert pressure and leads to dehumanised work environment which has substantial impact on their QWL. Lack of attention from management on issues related to psychosocial factors is one of the reasons. Thus, in light of humanising workplace, this research was initiated to investigate the relationship between psychosocial factors and QWL among the fastest growing workforce which will be responsible to transform Malaysia into a developed nation. A total of 453 valid responses were used from a sample of 600 questionnaires sent to randomly selected IS personnel employed in MSC organisations. The 76% of return rate was due to multiple approaches practised in collecting the survey questionnaires. The data collected were first explored using Exploratory Data Analysis (EDA) and reliability test prior to employing descriptive and inferential statistics using the SPSS.This study found that most of the IS personnel employed in MSC organisations experience moderate to high level of QWL. Organisational support, job dimension, job control and job demand show significant positive relationship with QWL. The components of organisational characteristics (co-worker support) and job characteristics (autonomy, task identity, task significance, psychological demand, emotional demand and skill discretion) are the major contributors of QWL. All the selected psychosocial factors, namely, job dimension, job control, organisational support, and job demand, are the major contributors of QWL. However, growth need strength (GNS) was not the major contributors. The selected psychosocial variables explained 49.3% of variance in QWL. The selected socio-demographic variables; personal profile (gender, age, educational level and monthly income); professional profile (total work experience, occupational category and work practices); and organisational profile (year of operations and nationality of the workforce) show significant difference in the mean of QWL. A highly demanding job with substantial control and support creates an active working condition that provides a continuous learning environment for continuous improvement. Hence, the IS personnel experience better QWL. This study recommends that the relevant authorities take precautionary action to maintain a higher level of QWL among IS personnel. Future research should include wider scope of psychosocial variables across various industries before providing additional input for strategic human resource planning for IS personnel in the country.